Evaluation of gastro protective effects of duranta repens extract against ethanol-induced gastric mucosal injuries in rats / Peshawa Yunis Aziz - Aziz, Peshawa Yunis (2013)
The objective of this study was to evaluate the gastro protective effects of Duranta repens ethanol extract against ethanol-induced gastric mucosal injuries in rats. The plant extract were evaluated for antioxidant, antiulcer and antibacterial activity. FRAP and DPPH assays were used for evaluating antioxidant activity (in vitro). Male rats (Sprague Dawely) were used for evaluating antiulcer activity. The rats were randomly divided into five groups. after that the groups were respectively pretreated with 10% tween twenty, omeprazole, 62.5, 125 and 250 mg/kg of Duranta repens leaf extract. Duranta repens extract was evaluated for in vivo toxicity. Antibacterial activity was evaluated by disc diffusion assay. In antiulcer study gross, histology, pH and mucus production were assessed. Furthermore, levels of superoxide dismutase (SOD) enzyme and malondialdehyde (MDA) of gastric tissue homogenate were measured. The results of antioxidant tests demonstrated that the FRAP value of plant extract is (979.3±0.01μmolFe(II)/g) in FRAP assay and IC50 value of plant extract is (29.7μg/ml) in DPPH assay. In antiulcer study the high dose of plant extract showed the best result, which significantly reduced the ulcer area to (170.66 ± 6.1mm2), with a very mild disruption in the surface epithelium without edema and leucocyte infiltration of the submucosal layer. Gastric mucus production was increased (0.64 ± 0.01mg), and acidity decreased (5.21 ± 0.08) in experimental groups treated with the plant extract compared to the ulcer control group. Moreover, the high dose of plant extract led to increase in SOD level to (11.45 ± 0.53 U/ml) and lowered MDA level to (12.90 ± 1.34μM). Acute toxicity test detected non-toxic effect of the plant extract. Duranta repens is a proper plant for healing gastric ulcer, and it can be suggested that Duranta repens leaf extract possess gastro protective activity against ethanol-induced gastric mucosal injuries. In antibacterial activity evaluation, all tested bacterial species were resistant to plant extracts.